2024
DOI: 10.3390/pharmaceutics16030327
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Scaffolds Incorporated with Silver Nanoparticles for the Treatment of Infected Wounds

Sibusiso Alven,
Blessing Atim Aderibigbe

Abstract: Bacterial infections are major problems in wound care due to their impact on the retarded process of wound healing, leading to chronic wounds. Most of the presently utilized wound dressing products exhibit poor antimicrobial properties. Wound dressings formulated from chitosan have been reported to be effective for treating infected wounds, resulting from the antibacterial properties of chitosan. The antibacterial properties of chitosan-based wound dressings can be further enhanced by incorporating metallic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 149 publications
0
1
0
Order By: Relevance
“…The incorporation of silver nanoparticles into chitosan dressings should be investigated further to mitigate drug toxicity, particularly for wounds requiring immediate treatment. This exploration should consider both in vitro conditions and in vivo wound environments, taking into account the inherent differences between them [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of silver nanoparticles into chitosan dressings should be investigated further to mitigate drug toxicity, particularly for wounds requiring immediate treatment. This exploration should consider both in vitro conditions and in vivo wound environments, taking into account the inherent differences between them [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of silver nanoparticles into chitosan dressings should be investigated further to mitigate drug toxicity, particularly for wounds requiring immediate treatment. This exploration should consider both in vitro conditions and in vivo wound environments, taking into account the inherent differences between them [39]. Our antimicrobial assays revealed that our electrospun samples' bactericidal efficacy is contingent on the type of bacteria and the polymer composition utilized.…”
Section: Biocompatibility Assessmentmentioning
confidence: 93%
“…Chitosan microspheres (CH-MS) were found to exhibit great potential as a drug delivery system and have been proposed both for controlled drug release and for improving the bioavailability of poorly water-soluble drugs [ 2 , 3 , 4 ]. Moreover, chitosan has shown antimicrobial and antibiofilm activity [ 5 ] and for this reason its use has recently been proposed for making dressings for the prevention of microbial infections [ 6 ]. However, there are a few drawbacks associated with chitosan, such as lack of stability and poor mechanical properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%